2016
DOI: 10.1002/smll.201503267
|View full text |Cite
|
Sign up to set email alerts
|

Ultralight Interconnected Metal Oxide Nanotube Networks

Abstract: Record-breaking ultralow density aluminum oxide structures are prepared using a novel templating technique. The alumina structures are unique in that they are comprised by highly aligned and interconnected nanotubes yielding anisotropic behavior. Large-scale network structures with complex form-factors can easily be made using this technique. The application of the low density networks as humidity sensing materials as well as thermal insulation is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Nanoscale production of materials is a useful strategy to prepare flexible materials with excellent recovery property . Macroscopic mechanical test is carried with a 20 nm deposited sample (Figure A‐C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoscale production of materials is a useful strategy to prepare flexible materials with excellent recovery property . Macroscopic mechanical test is carried with a 20 nm deposited sample (Figure A‐C).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, designing new porous structures to achieve extraordinary resilience for inorganic materials systems has become an area of focus. Three dimensional (3D) nanoporous materials composed of one dimensional (1D) building blocks including nanotubes and fibrous can potentially improve the mechanical strength and elasticity of metallic and ceramic materials. For example, Schaedler et al reported ultralight metallic microlattices with hollow tubes structure, which is able to recover with a height loss of ~5% after removal of 50% compression.…”
Section: Introductionmentioning
confidence: 99%
“…The current focus is synthesizing multifunctional materials with ultralow density, a high surface area, and mechanical robustness which are emphasized in energy storage devices. 388 These nanostructured materials have been devised to functionalize in energy storage devices being fabricated on the basis of a high surface area in which electrolyte ions can easily permeate, diffuse with high porosity through these functionalized electrode materials. [389][390][391] Many efforts have been devoted to incorporating metal oxide frameworks into graphene sheets resulting in 3D composite electrodes 392 as shown in Fig.…”
Section: Metal Oxide (Mo X ) Based Nanotube Network For Hybrid Supermentioning
confidence: 99%
“…To minimize the design complexity of the systems, Whitesides et al and other researchers have demonstrated various techniques for the full integration of electronic and microfluidic structures using printing electrodes on paper. The unique characteristics of the alumina nanotube/CNT hybrid system studied in this work make these structures ideal for integrated sensors for the sensitive detection of clinical, environmental, and food safety analytes. In particular, the extremely large surface area (∼ 265 m 2 g –1 ) provided by the alumina nanotubes and controlled fluid flow within the structure allowed for the detection of very low concentrations of analytes. Furthermore, the use of alumina nanotubes leads to faster mass transfer rates, resulting in lower limits of detection …”
Section: Introductionmentioning
confidence: 99%